The Influence of Environmental Awareness, Green Marketing, and Green Attribute Transparency on Purchase Intention Through Corporate Brand Image: A Case Study on Sensatia Botanicals Consumers in Indonesia - Pasaribu, Eiwanda Magdalena; Yulika Rosita Agrippina (Program MM Universitas Surabaya, 2026)
Purpose: This study aims to analyze the effects of environmental awareness, green marketing, and green attribute transparency on consumers’ purchase intentions toward environmentally friendly personal care products, with corporate brand image as a mediating variable. The novelty of this research lies in emphasizing green attribute transparency as a distinct determinant of purchase intention and in examining the mediating role of corporate brand image within the context of sustainability-oriented personal care brands in Indonesia. Method: This study used primary data collected through an online questionnaire distributed to 306 Indonesian consumers aged 18 years and above who are familiar with environmentally friendly personal care products. A non-probability purposive sampling technique was applied, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results: The findings indicate that environmental awareness, green marketing, and green attribute transparency positively influence purchase intention, with corporate brand image playing a supporting role in shaping consumer perceptions. Corporate brand image significantly mediates the effects of environmental awareness and green attribute transparency on purchase intention, but does not mediate the relationship between green marketing and purchase intention. These results highlight the importance of transparent environmental information beyond promotional claims, while future studies are encouraged to explore additional variables and alternative research designs to strengthen explanatory power.